ANALISIS FINANSIAL USAHA TERNAK DOMBA BATUR DI KABUPATEN BANJARNEGARA - Suryani Br Manik; Siswanto Imam Santosa; Wulan Sumekar (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
The research head for know find out the financial analysis of Batur sheep livestock in Banjarnegara Regency. The sample collection technique using a multistage random sampling. Respondents taken as many as 120 people and chosen at random. Data result has been analysis by descriptive. This result point out that value of NPV in amount of Rp. 1.023.719,31; B/C ratio 1,09; IRR 26,00% and investment return at two years. Result showed that Batur sheep livestock in Banjarnegara regency otherwise worthed in financial. The showed in NPV value more that zero that mean benefit accepted more than cost be taken out. B/C ratio value more than 1 means income more than expensive into get benefit. IRR value more than credit interest BRI applicable current in amount of 12,3% that mean profit income obtain more than bank interest effort is feasible to operate.